Numerical Simulation of the 2017 Xinmo Catastrophic Landslide Considering Entrainment Effect - Chen, Qin; Fan, Gang; Zhou, Jia-wen (Frontiers in Earth Science, 2020)
The mass movement process of the 2017 Xinmo catastrophic landslide was simulated using the discreet element method (DEM). Field investigation indicates that the basal entrainment is a typical feature of this landslide. Hence, the entrained colluvium on the sliding path is considered in the DEM model. According to the terrain elevation data before and after sliding, the slope geometry is divided into three parts, sliding bed, sliding body and colluvium on the path. The blocks are generated in MATLAB and a fill-remove method has been used to produce the loose colluvium. The key parameter, contact friction angel, which controls the mobility of mass movement, has been obtained through displacement back analysis. The simulated deposit area and main sliding time coincide with actual landslide characteristics. Simulation results indicate that the colluvium is pushed to the bottom of the Songpinggou Valley by the sliding body. The local topography has a significant influence on the sliding direction. Some typical phenomena of substrate entrainment including frontal ploughing, mass spray, shear zones in substrate, thickened substrate and basal abrasion are observed in the DEM simulation. During the entrainment process, the frontal ploughing, or the thrust, plays an important role in resulting in substrate failure compared with basal abrasion. After the failure of the whole colluvium, the magnitude of thrust descends quickly but is still slightly larger than that of shear. Entrainment of dry material on slope leads to more friction energy consumption and reduces the mobility of mass movement. This work shows good capability of simulating entrainment of dry materials using discreet element method and highlights the significance of ploughing relative to the basal abrasion under conditions of limited path material supply.